2021
DOI: 10.1007/s00125-021-05533-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diet quality during pregnancy is associated with biomarkers of metabolic risk among male offspring

Abstract: Aims/hypothesis Limited data exist on the association between maternal diet quality during pregnancy and metabolic traits in offspring during early childhood, which is a sensitive period for risk of obesity-related disorders later in life. We aimed to examine the association of maternal diet quality, as indicated by the Healthy Eating Index-2010 (HEI), in pregnancy with offspring metabolic biomarkers and body composition at age 4-7 years. Methods We used data from 761 mother-offspring pairs from the Healthy St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 59 publications
(82 reference statements)
1
14
0
Order By: Relevance
“…Thus, from a fetal programming hypothesis, it seems as if the male fetus may be more sensitive to an excess of thyroid hormones in relation to pubertal development. Previous studies have identified a similar male-specific effect to an intrauterine exposure perhaps due to an increased vulnerability of the male fetus (50)(51)(52). Additionally, we found tendencies of associations between all 3 maternal thyroid diseases and pubertal development in sons when the disease was diagnosed before birth perhaps due to inadequate treatment during pregnancy.…”
Section: Discussionsupporting
confidence: 76%
“…Thus, from a fetal programming hypothesis, it seems as if the male fetus may be more sensitive to an excess of thyroid hormones in relation to pubertal development. Previous studies have identified a similar male-specific effect to an intrauterine exposure perhaps due to an increased vulnerability of the male fetus (50)(51)(52). Additionally, we found tendencies of associations between all 3 maternal thyroid diseases and pubertal development in sons when the disease was diagnosed before birth perhaps due to inadequate treatment during pregnancy.…”
Section: Discussionsupporting
confidence: 76%
“…For example, Francis et al studied 761 mother-offspring pairs to assess the relationship between the Healthy Eating Index (HEI) in pregnancy and offspring body weight, fat mass, and metabolic measures. Results showed an inverse correlation between maternal HEI and glucose, insulin, HOMA-IR, and adiponectin in male, but not female children [42]. Animal studies from our laboratory have also shown that maternal obesity is associated with glucose intolerance, hyperinsulinemia, increased leptin level, and hyperphagia in male rat offspring [43].…”
Section: Discussionmentioning
confidence: 58%
“…We assessed maternal CHO intake in quartiles to allow for non-linear associationsan approach that is widely accepted and conventional in nutritional epidemiology (e.g. (35)(36)(37) ). The estimates of interest were pairwise contrasts between the second, third and fourth quartiles of maternal CHO intake v. the first quartile as the referent, along with P-trend and type 3 P-differences to assess statistical significance of associations.…”
Section: Discussionmentioning
confidence: 99%